Newly diagnosed nasopharyngeal carcinoma with intracranial extension complicated with multiple thrombotic complications - Yap, Yoon Chin; Lo, Zhen Zhen; Heng, Sophia Si Ling (Elsevier Inc, 2023)
Cavernous sinus thrombosis (CST) is a rare and life-threatening condition, it usually presented in septic patient due to infection of central face or paranasal sinuses.1,2 Aseptic causes are less common, is a thrombotic process and often following trauma and prothrombotic event.